6th AIAA Aviation Technology, Integration and Operations Conference (ATIO) 2006
DOI: 10.2514/6.2006-7809
|View full text |Cite
|
Sign up to set email alerts
|

Flow Visualization Study on the Effect of a Gurney Flap in a Low Reynolds Number Compressor Cascade

Abstract: IntroductionThe first century of heavier-than-air powered flight has been dominated by the desire to fly "faster, higher, and farther." Fulfilling this desire led to the development of the gas turbine driven turbojet. Since their introduction more than six decades ago, gas turbine driven engines have become quite powerful in terms of thrust produced 1 while achieving significant improvements in fuel efficiency 2 and reductions in maintenance costs 3 . Today, gas turbine driven turbofans and turboprops dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…There is a significant increase in lift with only a small increase in drag as long as the flap height scales with the local boundary layer thickness. Despite their widespread use in aeronautics (Lee [1], Lee and Su [2] and Wang et al [3]), very little research work has been done on turbomachinery (Byerley et al [4], Chen et al [5], Greenblatt [6], Janus [7] and Myose et al [8]). An effort has been made here to find the effectiveness of Gurney flaps on the performance of centrifugal fan.…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant increase in lift with only a small increase in drag as long as the flap height scales with the local boundary layer thickness. Despite their widespread use in aeronautics (Lee [1], Lee and Su [2] and Wang et al [3]), very little research work has been done on turbomachinery (Byerley et al [4], Chen et al [5], Greenblatt [6], Janus [7] and Myose et al [8]). An effort has been made here to find the effectiveness of Gurney flaps on the performance of centrifugal fan.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental static pressure distribution and total pressure loss coefficient agreed well with the computational results. Myose et al (1996) conducted flow visualization study with Gurney flap in compressor cascade at low Reynolds number and showed that Gurney flap delayed the stall at large incoming flow angles. Greenblatt (2011) used large Gurney flaps in an axial fan and studied about the effect of height and thickness of Gurney flap.…”
Section: Introductionmentioning
confidence: 99%